The extent of robot eligibility to practice legal and judicial functions and professions: legal evaluation study on personality and responsibility - Alejili, Ahmed Salem Ahmed; Laeba, Muhammad (USIM Press, Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2025)
As a result of the digital revolution, robots have recently dominated various aspects of life, particularly in the professional and occupational fields, including legal professions and practices. This has made them real partners and even competitors to human beings. Some optimistic teams consider this as an opportunity to harness technology for the development of these professions, while pessimistic ones view it as a threat to employment opportunities in the legal field, as robots replace human partners. Without favoring one viewpoint over another, a study emphasizes the importance of conducting a comprehensive evaluation of the personality and responsibility aspects of robots, as well as reviewing legal professions and practices to determine the suitability of robots for performing these tasks. This requires an objective and extensive assessment of the robot's personality and scope of responsibility, based on relevant legal rules using descriptive, analytical, and comparative approaches. Additionally, it involves reviewing the objective aspects of legal professions and practices in light of the legal nature of robots. The study concludes that artificial intelligence can be utilized, and robots can be employed in administrative, organizational, procedural, and modeling aspects of the legal field. However, legal work that requires estimation, wisdom, critical thinking, balancing interests, assessing situations, interpreting laws, and weighing texts remains the domain of humans. This is due to the robot's inability to bear responsibility and go beyond its programmed limits without consulting the programmer. Therefore, these types of legal tasks remain exclusively reserved for qualified humans capable of making appropriate decisions.